Three main disputes in Japan’s Foreign Policy. - Arin., R. G. (Journal of Oriental Studies, 2016)
The given article discusses the three main disputes such as pacifist-militarist,insular-maritime and west-orient, which has strong effect on Japanese Foreign Policy agenda. Also the article considers the general descriptions of their emergence, historical significances, theoretical substantiation, reflections in practice, mutual links, historical periods and their present condition.